PENDIDIKAN ISLAM DI PAKISTAN - Samdani Samdani (EDUCATIONAL JOURNAL : General and Specific Research, 2021)
The educational problem that occurs in Pakistan is that there are statements that identify some religious education institutions/madrasahs that are involved in terrorist movements. Meanwhile in Indonesia, there are also issues that identify the same thing as what happened in Pakistan. Another problem that is almost the same as in Indonesia is that there are still many children dropping out of school in Pakistan as well as in Indonesia, even though there is a law that regulates compulsory education for children but the state has not done much to serve the mandate of the law. there is punishment for parents who do not carry out compulsory education as mandated by each compulsory education law both in Pakistan and Indonesia.